ЭКОНОМИКА КАРАКАЛПАКСТАНА – ВЗГЛЯД В БУДУЩЕЕ - Умаров, Е.К. (SCIENCE and SOCIETY, 2017)
In article, coming from decision of the exit counsels foresight Uzbekistan considered the developments social-economic systems Karakalpakstana in vomit and segment urgent prospect. In this collecting are put problem of the efficient use resource potential of the region and making the new branches to industry.